1999
DOI: 10.1164/ajrccm.159.5.9810054
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Resting Hypercapnia and Physiologic Parameters before and after Lung Volume Reduction Surgery in Severe Chronic Obstructive Pulmonary Disease

Abstract: Patients with severe chronic obstructive pulmonary disease (COPD) have varying degrees of hypercapnia. Recent studies have demonstrated inconsistent effects of lung volume reduction surgery (LVRS) on PaCO2; however, most series have excluded patients with moderate to severe hypercapnia. In addition, no study has examined the mechanisms responsible for the reduction in PaCO2 post-LVRS. We obtained spirometry, body plethysmography, diffusion capacity, respiratory muscle strength, 6-min walk test, and incremental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Several studies have assessed the effects of LVRS on diaphragm strength by measuring Pdi sniff , Pdi max , or Pdi tw before, and 1 to 24 mo after the procedure (2, 12, 26, 29 -32, 41, 53, 58). These studies are qualitatively consistent, all showing an increase in the pressure-generating capacity of the muscle after surgery; four studies also showed increases in MIP (12,41,53,58). The increase in MIP and Pdi sniff was already present at 1 mo after LVRS in one study (58), and in the study by Bellemare et al (2), Pdi max (but not Pdi tw ) continued to increase throughout the first postoperative year.…”
Section: Diaphragm Strengthsupporting
confidence: 62%
“…Several studies have assessed the effects of LVRS on diaphragm strength by measuring Pdi sniff , Pdi max , or Pdi tw before, and 1 to 24 mo after the procedure (2, 12, 26, 29 -32, 41, 53, 58). These studies are qualitatively consistent, all showing an increase in the pressure-generating capacity of the muscle after surgery; four studies also showed increases in MIP (12,41,53,58). The increase in MIP and Pdi sniff was already present at 1 mo after LVRS in one study (58), and in the study by Bellemare et al (2), Pdi max (but not Pdi tw ) continued to increase throughout the first postoperative year.…”
Section: Diaphragm Strengthsupporting
confidence: 62%
“…A study by Yusen and coworkers showed that the proportions of patients using supplemental oxygen at rest and with exercise fall significantly 6 months after LVRS (53 to 15% for use at rest and 95 to 46% for use on exercise) (41). Although patients with severe hypercapnia were excluded from most studies, patients with modest hypercapnia did show improvement to the normal or near-normal range (41,42).…”
Section: Pulmonary Function and Gas Exchangementioning
confidence: 99%
“…This mechanism may more properly be thought of as a measurement error, although it does reflect emphysematous pathophysiology. Interestingly, improvements in gas transfer appear to be a consistent feature of BLVR whereas following LVRS, perhaps because the technique inevitably requires the removal of some relatively normal lung tissue, it has not improved in a number of studies [1,20], although this has not been a universal finding [21,22].…”
Section: Mechanisms For Success or Failurementioning
confidence: 99%